Towards a Working Definition of Negotiation in Telecollaboration: Analysis of Teletandem Oral Sessions1 - Aranha, Solange [UNESP] (2022)
As digital technology advances, geographically distant learners have been engaging in cross-cultural communication and negotiation via telecollaborative projects. Research has shown that negotiation of meaning is crucial for effective communication in these scenarios, but more studies on other types of negotiation are needed, given its importance for establishing cooperation. This paper aims at exploring the negotiation patterns between dyads in ten sessions selected from a Multimodal Teletandem Corpus and provides a working definition of negotiation in telecollaboration. The participants, who were university students in Brazil and abroad and were enrolled in language classes, met online to help with practicing each other's language and were expected to exchange information about themselves in the first synchronous session. Through a qualitative analysis of the transcripts of the ten sessions, we identified moments in which the conversation was suspended to negotiate meaning, technology issues, separation of languages, and aspects related to the tasks requested by teachers. Our analysis shows that negotiation in telecollaboration may be motivated by aspects internal to the conversation, such as meaning, or by external factors, as with problems with equipments, tasks, or with deciding the language to be spoken. The findings suggest that negotiation serves an essential purpose, as it allows participants to make collaborative decisions and resolve conflicts that could otherwise prevent conversation from continuing. The results may prove useful for researchers and practitioners interested in telecollaboration, aiming to design experiences and guide participants through learning in such contexts.